Challenges and Perspectives of Computerassisted Instruction in Medical Education - Haag, M.; Singer, R.; Bauch, M.; Heid, J.; Hess, F.; Leven, F.J. (Methods of Information in Medicine, 2007)
Objectives: In this paper we discuss solutions to the problem that medical teachers and students do not use modern computer-assisted instruction systems in medical education as much as expected by their developers.Methods: As an example for a modern problem-based CAI system we introduce the CAMPUS shell system for case-based training in medicine.Results: CAMPUS has received several awards and positive evaluation results. Nevertheless, the usage of such systems in courses and for self-study could be increased.Conclusions: Curricular integration of CAI as well as further improvements on existing CAI systems to increase the usage in medical education is essential.
Keywords: Computer-assisted instruction; medical education; problem-based learning